Analisis Pengujian Stasiun Solo Jebres Setelah Beroperasinya Jalur KRL Yogyakarta – Solo: Analysis Of The Solo Jebres Station Testing After Yogyakarta – Solo Electrification Line Operation - Burhanudin Suni; Yuwono Wiarco; Rusman Prihatanto; Wahyu Tamtomo Adi; David Malaiholo (Media Ilmiah Teknik Sipil, 2023)
Data from the Directorate General of Railways states that in 2022, the Yogyakarta – Solo electric train will carry an average of 11,815 passengers/day and since February 2021 the total number of passengers that can be carried has reached 3,153,4750 passengers. This is proof of the great public interest in public transportation. The increase in passenger numbers is offset by improvements in railway infrastructure, especially at stations. This research aims to evaluate the suitability of the station by conducting tests based on Ministerial Regulation Number 30 of 2011 and to determine the implementation of minimum service standards at Solo Jebres Station after the operation of the electric train. After testing the station, some facilities were not adequate, namely the length of the platform used for boarding and alighting passengers. Meanwhile, other facilities are adequate, such as platform height, free space and buildings. Minimum service standards at Solo Jebres Station for long-distance train station are 78 facilities comply and 17 facilities do not comply with the minimum service standards, while for electric train station 79 facilities comply and 16 facilities do not comply with these standards